Production of high temperature grease using spent bleaching earth (SBE) - Nor Azlina, Mohd Ali (2010)
Nowadays, the disposal problem of Spent Bleaching Earth (SBE) from oil palm industry has become a serious environmental issue. Therefore, attempt was made in this research to utilize the SBE as raw material in the production of high temperature grease. The scope of this research includes preparation of calcium fluoride as thermal resistance additives, grease preparation and analysis on the grease produced. The parameters studied for grease preparation are effect of different ratio of SBE and fumed silica as thickener and effect of mixing time. The ratios of SBE used in grease formulation were varied from 100 wt. % to 60 wt. % of thickener weight. The best ratio chosen from grease formulation is based on the dropping point test before it was further used for second parameter. As a second parameter, the mixing time of grease preparation was varied at 1, 2, 3, 4 and 5 hours. The grease produced was analyzed for dropping point, worked penetration, copper corrosion, organic content using FTIR and metal content using AAS. The results obtained were compared to the National Lubricating Grease Institute (NLGI) Guide to classify the grease. Results indicate that the best ratio for grease formulation is 90% of SBE and 10% of fumed silica. Therefore, the usage of fumed silica which is very expensive can be reduced. Results also shows that the consistency of grease decreased as the mixing time increased. With refer to NLGI standard, the consistency of all grease at mixing time 1 to 5 hour is in the range of 2 to 4 grade number and can be classified as high temperature grease since its dropping point is higher than 260oC. As a conclusion, the findings from this research has the high potential to help in solving the environmental problem on SBE disposal which is in line with the government campaign to reduce waste in daily life and indirectly can reduce the production cost with this SBE based grease.